PERANCANGAN IKLAN INSTASTORY DAILY SEBAGAI PESAN BIJAK BERKENDARA DI JALAN RAYA - sahisnu, diptya aristo (DeKaVe, 2020)
The news of the traffic is very updated Lot of the day, from the violation of the community to inform social media, namely to remind the danger of violations of people in the highway. Congestion becomes a perbicangan and the idea that is often displaced in the group as well as lacking the wise attitude of driving on the highway.Instastory daily AD Design is the most suitable approach for communicating the wise message of this drive in Hengel, quality, and interrated Instastrory has the advantage of interactive stuff, method of 101 design method by Vijay Kumar Liquid One of the literary solver to be able to visualize sponsored advertisements, as well as communicative because it can do in dailly.This ad design titled " Pesan Bijak Bijak berkendara di Jalan Raya " will be able to visualize a wise message of driving in 15 seconds and can be a profile Instagram account. A person can Mauri a registered ad is published through an Instagram profile with a spotlight menu. This promotion will not only be sponsored but also used in social promotion as a community with optimal results